A SPH numerical wave flume with non-reflective open boundary conditions. (1st September 2018) - Ni, Xingye; Feng, Weibing; Huang, Shichang; Zhang, Yu; Feng, Xi
Abstract: In this paper, a numerical wave flume with full functions of wave generation and absorption is proposed under the framework of Weakly Compressible Smoothed Particle Hydrodynamics (WCSPH). In contrast to the conventional SPH numerical wave flumes using wave paddles and sponge layers, the wave generation and absorption in this paper are implemented using non-reflective open boundary conditions, which are capable of generating multiple types of waves, including solitary waves, linear and second-order regular waves. Passive and active wave absorption are available for transmitting incident waves and preventing secondary reflections. Steady or unsteady flows can also be defined during wave generation and absorption to set up numerical wave-flow flumes. The results on a series of validation cases indicate that this SPH numerical wave flume not only performs satisfactorily in conventional wave generation and absorption and nonlinear wave-structure interaction simulations but also has the following three advantages: 1) It avoids using the sponge layers to shorten the flumes, which improves the efficiency; 2) it keeps the mean water level steady and prevents water level shifting; and 3) it implements steady/unsteady flow and wave-flow interactions to model a wider range of hydrodynamic problems. Highlights: A SPH numerical wave flume is implemented using non-reflective open boundary conditions for wave generation and absorption. Various types of waves can be generated, and passive and active wave absorption are available. Wave-flow interactions can be simulated in this NWF. The NWF has higher computational efficiency than conventional SPH flumes.